ISOLATION OF LACTIC ACID BACTERIA AS A POTENTIAL PROBIOTIC IN DANGKE, A TRADITIONAL FOOD FROM BUFFALO MILK IN CURIO THE DISTRICT OF ENREKANG - Nur, Fatmawati (Proceeding Buffalo International Conference, 2013)
This research is a preliminary study to explore potential probiotics of Lactic Acid Bacteria (LAB) in dangke, a traditional food from buffalo milk in Curio the district of Enrekang.Â  Isolation of LAB performed using the selective medium de Man Rogosa Sharpe Agar. LAB will show clear zone on MRS medium after the addition of the indicator in the form of CaCO3 and incubated for 24 hours. Selection is done by observing the cell morphology and Gram staining. Further testing with the biochemical properties of sugar fermentation test. To assess their probiotic ability, tolerance of low pH were examined. The results showed that lactic acid bacteria isolats obtained consists of two species of Lactobacillus plantarum and Lactobacillus fermentum, and both of them can survive at pH 2. Isolats of L. fermentum and L. plantarum in dangke are derived from buffalo milk showed potential as a candidate probiotic bacteria.